Transcription Factor GmWRKY142 Confers Cadmium Resistance by Up-Regulating the Cadmium Tolerance 1-Like Genes - Cai, Zhandong; Xian, Peiqi; Wang, Huan; Lin, Rongbin; Lian, Tengxiang; Cheng, Yanbo; Ma, Qibin; Nian, Hai (Frontiers in Plant Science, 2020)
Cadmium (Cd) is a widespread pollutant that is toxic to living organisms. Previous studies have identified certain WRKY transcription factors, which confer Cd tolerance in different plant species. In the present study, we have identified 29 Cd-responsive WRKY genes in Edamame [Glycine max (L.) Merr.], and confirmed that 26 of those GmWRKY genes were up-regulated, while 3 were down-regulated. We have also cloned the novel, positively regulated GmWRKY142 gene from soybean and investigated its regulatory mechanism in Cd tolerance. GmWRKY142 was highly expressed in the root, drastically up-regulated by Cd, localized in the nucleus, and displayed transcriptional activity. The overexpression of GmWRKY142 in Arabidopsis thaliana and soybean hairy roots significantly enhanced Cd tolerance and lead to extensive transcriptional reprogramming of stress-responsive genes. ATCDT1, GmCDT1-1, and GmCDT1-2 encoding cadmium tolerance 1 were induced in overexpression lines. Further analysis showed that GmWRKY142 activated the transcription of ATCDT1, GmCDT1-1, and GmCDT1-2 by directly binding to the W-box element in their promoters. In addition, the functions of GmCDT1-1 and GmCDT1-2, responsible for decreasing Cd uptake, were validated by heterologous expression in A. thaliana. Our combined results have determined GmWRKYs to be newly discovered participants in response to Cd stress, and have confirmed that GmWRKY142 directly targets ATCDT1, GmCDT1-1, and GmCDT1-2 to decrease Cd uptake and positively regulate Cd tolerance. The GmWRKY142-GmCDT1-1/2 cascade module provides a potential strategy to lower Cd accumulation in soybean.